The differences in metabolic responses between dietary orotate and adenine in lipid profiles of serum and liver tissues (Medical Journal of Indonesia, 2010)
Aim: Objectives to evalate the differences in metabolic responses between dietary orotic acid and adenine in lipid profiles of serum and liver tissues.Methods: Rats were paired-fed 1.0 % orotic acid (orotic acid group) and 0.25 % adenine (adenine group) diets or a non-supplemented diet (control group) for 10 days. Serum lipid concentrations were measured using enzyme assay kits. Lipids of liver tissues were extracted and the lipid contents were  determined.Results: Serum lipid concentrations (in mg/dL) of adenine group tended to increase whereas those levels decreased in orotic acid group compared to control group. The serum triglyceride (TG) concentrations of control, orotic acid, and adenine groups were (78.1±14.9), (69.0±23.6), and (136.1±21.6); phospholipids (PL): (109.2±11.5), (93.3±10.5), and (131.3±11.0); total cholesterol: (53.7±4.6), (42.9±6.5), and (68.1±5.8); and high-density lipoprotein (HDL)-cholesterol: (35.4±2.7),(33.0±3.0), and (44.7±2.7), respectively. Furthermore, liver TG content of orotic acid group markedly increased. The increase was approximately by 10-fold in comparison to other groups (P<0.05). The lipid contents of liver tissues (in mg/g tissue) in ordinarily of those three groups for TG were (11.4±1.3), (123.5±15.2), and (11.9±1.2); PL: (27.1±0.8), (25.4±1.3), and (30.7±0.6); and the total cholesterol: (2.73±0.09), (2.34±0.12), and (2.91±0.08), respectively. The liver PL and cholesterol content of adenine group increased by 21% and 25% than that of orotic acid group, but both lipid levels of the latter group increased by 7% and 15%, respectively, than that of the control group.Conclusion: Dietary adenine enhances the serum TG, PL, cholesterol, and HDL-cholesterol and the liver PL and cholesterol but without alters the liver TG levels. Dietary orotic acid, however, attenuates these serum lipid levels but retains those lipids  synthesized in liver cells, mainly TG. (Med J Indones 2010; 19:217-22)Keywords: Adenine, liver lipids, lipogenesis, orotic acid, serum  lipids